Optimization of process parameters on EDM milling of stainless steel AISI 304 - A.K.M, Asif Iqbal; Khan, Ahsan Ali (Trans Tech Publications, Switzerland, 2011)
Electrical Discharge Machining (EDM) is one of the most widely used non conventional machining processes for removing material from workpiece by means of a series of repeated electric discharges. This process is now one of the main techniques used in die production and has good accuracy and precision with no direct physical contact between the electrodes so that no mechanical stress is exerted on the workpiece. Electrical discharge milling (ED-milling) is an emerging technology where a cylindrical tool electrode follows a programmed path in order to obtain the desired shape of a part. The current investigation aims to optimize the process parameters during EDM milling of stainless steel by using copper electrode. The selected input parameters used for the study are voltage, rotational speed of the electrode and feed rate while the responses are material removal rate (MRR), electrode wear ratio (EWR) and surface roughness (Ra). Response surface methodology is used in the study. The experimental design is formed by using design expert software. Central Composite design (CCD) is used to identify the optimum operating condition in order to obtain maximum MRR, minimum EWR and minimum Ra as response. The result shows that the machining parameter setting of voltage 120 V, rotational speed of electrode 1200 rpm and feed rate 4μm/s, gives optimized responses MRR 5.0259 x 10-3 mm3/min, EWR 53% and Ra 0.79 μm.